2023
DOI: 10.1186/s40364-022-00441-w
|View full text |Cite
|
Sign up to set email alerts
|

MiR-124-3p impedes the metastasis of non-small cell lung cancer via extracellular exosome transport and intracellular PI3K/AKT signaling

Abstract: Background Metastasis is a significant factor that affects the survival of patients with non-small cell lung cancer (NSCLC). Nevertheless, the molecular regulatory mechanism underlying the metastasis is currently not fully understood. This study aims to identify the important role of miR-124-3p in metastasis of NSCLC, thereby providing a potential therapeutic intervention. Methods Exosome secretion was determined by Nanoparticle Tracking Analysis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…(δ-like canonical notch ligands delta-like 4 protein) draws attention to interaction with miR-124 in neural stem cell differentiation (Jiao et al, 2017). In other studies, miR-124-3p was shown to suppress the invasiveness and metastasis of hepatocarcinoma cells (Majid et al, 2020) and nonsmall cell lung cancer cells (Zhu et al, 2023) which indicates the role of miR-124-3p on metastasis. In addition, overexpression of miR-124-3p in human glioblastoma multiforme and stem cells derived from mouse neural brain tumors was shown to induce conversion to the neural phenotype (Silber et al, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…(δ-like canonical notch ligands delta-like 4 protein) draws attention to interaction with miR-124 in neural stem cell differentiation (Jiao et al, 2017). In other studies, miR-124-3p was shown to suppress the invasiveness and metastasis of hepatocarcinoma cells (Majid et al, 2020) and nonsmall cell lung cancer cells (Zhu et al, 2023) which indicates the role of miR-124-3p on metastasis. In addition, overexpression of miR-124-3p in human glioblastoma multiforme and stem cells derived from mouse neural brain tumors was shown to induce conversion to the neural phenotype (Silber et al, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…Patients with above-median sEV levels had a poorer prognosis, with a 2.4 times higher risk of progression and 3 times higher mortality than patients with below-median levels, in whom the risk of death was reduced by almost 70%. Furthermore, having shown that the sEV content of these patients is rich in miR-124, the fact that other authors have found an opposite prognostic risk when using the tissue expression levels of miR-124 [99], and that miR-124 can act as a negative regulator of metastasis in lung cancer through targeting the GTPases responsible for exosome export [66,100], supports our hypothesis regarding the active expulsion of tumor suppressor miRNAs by cells during carcinogenesis in lung cancer, even in early stages, to promote the progression of the disease. Conversely, we did not find any association with the prognoses of NSCLC patients when we analyzed the levels of miR-132 in sEVs, suggesting that miR-132 might not be a good candidate for monitoring advanced NSCLC progression.…”
Section: Discussionmentioning
confidence: 99%
“…It plays a role in both breast and lung cancer [48] and was shown to suppress metastasis of lung cancer. [49] TRIM71 (Tripartite Motif Containing 71, LIN41) is a gene that encodes an E3 ubiquitin-protein ligase, which plays a role in the G1-S phase transition of the cell cycle. TRIM7 negatively regulates the NF-kappa B signaling pathway in lung cancer by degrading p65.…”
Section: Pathobiological Mechanisms Of Hypomethylated Genes and Promo...mentioning
confidence: 99%